Regional trending topics mining from real time Twitter data for sentiment, context, network and temporal analysis - Mousumi Hasan; Mujiba Shaima; Quazi Saad ul Mosaher (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska)
Twitter's tremendous impact extends from national to international affairs, covering domains such as religion, entertainment, environment, and politics. Unlike other social media platforms, Twitter offers researchers an open data source for multifaceted studies, motivating us to delve into regional trending topics, analyzing associated sentiments, context, networks, and temporal patterns. Using machine learning techniques combined with the VADER algorithm, we conducted a comprehensive analysis involving text, metadata, contextual cues, media, links, and historical data. In this study, we conducted an extensive Twitter mining operation on June 6, 2024, focusing on the ten most developed countries to explore sentiments associated with sustainable technology in industry. The insights derived from this research are pivotal for policymakers, industry stakeholders, and researchers, offering a nuanced understanding of public opinion on sustainable technology. Our findings underscore the potential of social media mining as a powerful tool for gauging public sentiment and informing strategic decision-making in the realm of sustainable industrial practices.